A cystic ring-enhancing cerebellar lesion. (June 2017) - Wang, Qiguang; Liu, Wenke; Cheng, Jian; Hui, Xuhui
Highlights: An important differential diagnosis in Gd-enhanced MRI with cystic ring-enhancing was made. A new category of hemangioblastoma has been presented. The operation strategy of cystic hemangioblastoma with enhanced wall thickness seems different.